Development and validation of a simulator for wireless data acquisition in gas turbine engine testing. Issue 3 (1st September 2013) - Dai, Xuewu; Mitchell, John E.; Yang, Yang; Glover, Ian; Sasloglou, Konstantinos; Atkinson, Robert; Panella, Isabella; Strong, John; Schiffers, Werner; Dutta, Partha
Abstract : Owing to its cable‐free deployment, wireless sensor networks (WSNs) have drawn great attention as a new technique for industrial data acquisition. However, the harsh environment of the gas turbine engine provides a number of challenges to deployment of wireless sensors. A definitive study of the impact of harsh environments on WSNs is currently lacking, which represents an obstacle to WSN's deployment in safety‐critical industrial instrumentation and automation. In this study, the authors report the test results of applying WSNs to data acquisition in gas turbine engine testing and the development of a realistic software simulator with the purpose of de‐risking the wireless data transmission technology in a project called WIDAGATE (wireless data acquisition in gas turbine engine testing). This study provides an overview of the simulation platform developed and investigates how small‐scale tests of a WSN deployed on a real engine were used to validate and improve the simulator platform. This work proposes realistic modelling of the physical layer (radio channel) when subject to interference in harsh industry environment during aero‐engine testing. Based on the validated, realistic physical layer model, different medium access control protocols are simulated to demonstrate how this improved simulator can be used to select an appropriate protocol.